2013
DOI: 10.1111/sbr.12016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep habits and knowledge after an educational sleep program in 12th grade students

Abstract: The objective of this research was to evaluate the effect of an education program using the meaningful learning approach on sleep knowledge and habits of 12th grade students. Thirty‐four student volunteers (aged 16.8 ± 0.6 years) were divided into intervention (Sleep Education Program – SEP) and control groups. Sleep knowledge and habits were assessed by the “health and sleep” questionnaire. Also, the students filled out a sleep diary and the Karolinska Sleepiness Scale by one week (Stage 1). These procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
2
32
1
2
Order By: Relevance
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
“…Three teams from Australia [17][18][19] and one from Brazil 28 recognized that their sleep education programs would be improved by factoring in theoretical guidelines, even suggesting in one study 28 that the lack of change was due to a poor theoretical basis. Social cognitive behavior theory, 17 motivational interviewing, 18 mindfulness based cognitive therapy, 19 and meaningful learning approaches 28 were the theories reported. The motivation to change was often related to the degree of dysfunctional sleep patterns at baseline and was less successful in changing behavior when the sleep patterns were better at baseline.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the review, some other school-based sleep education programs have emerged, but they are challenged by the same methodological concerns. [6][7][8] Common ingredients in many of these programs include coverage of topics such as typical sleep patterns, information about the function of sleep, and sleep hygiene, but some of have also covered social and cognitive aspects of sleep-health behaviors as well as increasing motivation to change. Additionally, there is wide variability in delivery format, duration of program, and outcomes.…”
Section: O M M E N T a R Ymentioning
confidence: 99%